Temperature and field dependent magnetization in a sub-μm patterned Co/FeRh film studied by resonant x-ray scattering. (19th April 2016) - Lounis, Lounès; Spezzani, Carlo; Delaunay, Renaud; Fortuna, Franck; Obstbaum, Martin; Günther, Stefan; Back, Christian H; Popescu, Horia; Vidal, Franck; Sacchi, Maurizio
Abstract: We studied the temperature and field dependence of the magnetization in a Co/FeRh/MgO(0 0 1) film patterned into a matrix of sub- μ m sized rectangles, using element selective resonant scattering of polarized soft x-rays. We show that it is possible to reverse partially the magnetization of the Co layer in a thermal cycle that crosses the FeRh antiferromagnetic to ferromagnetic transition. Our results support interest in patterned Co/FeRh films and their potential for achieving temperature induced magnetization switching.